Echocardiographic assessment of left ventricular myocardial strain, as a non-invasive method for diagnosing pulmonary hypertension in patients with end-stage chronic kidney disease - M. Sh. Khubutiya; E. V. Shuvalova; L. T. Khamidova; A. A. Ivannikov; A. G. Balkarov; I. V. Dmitriev; Kh. G. Alidzhanova (Трансплантология (Москва), 2023)
Background. Pulmonary hypertension is a common complication of chronic kidney disease, with incidence of up to 50%. Currently, the prognostic significance of non-invasive diagnostic methods for pulmonary hypertension in patients with chronic kidney disease remains relevant.Aim. To determine the significance of transthoracic echocardiography in diagnosing pulmonary hypertension in patients with end-stage chronic kidney disease.Material and methods. The study group consisted of 53 patients with chronic kidney disease stage 5D who were evaluated for kidney transplantation at the N.V. Sklifosovsky Research Institute for Emergency Medicine in 2022. A control group was represented by 24 healthy volunteers. Transthoracic echocardiography was performed on all patients according to a standard protocol, with determination of left ventricular myocardial strain indices.Results. A statistically significant correlation was found between the left ventricular global longitudinal strain and pulmonary artery systolic pressure r=0.488 (p<0.001), as well as between the left ventricular global circumferential strain and pulmonary artery systolic pressure (r=0.545, p<0.001). Regression analysis showed that an increase in pulmonary artery systolic pressure by 1 mmHg increased the odds of lethal outcome by 13% (Odds ratio: 1.13; 95% Confidence interval: [1.05;1.22], p=0.002).Conclusions. Hemodialysis patients are characterized by the development of pre-capillary pulmonary hypertension, which significantly affects their prognosis. Determination of left ventricular myocardial strain indices based on echocardiography provides additional information on the hemodynamics of the pulmonary circulation without using invasive diagnostic methods.